Urine inflammatory protein levels decrease following kidney transplantation - Elizabeth Spiwak; Corina Nailescu; David S. Hains; Marah Kolner; Samual Arregui; Andrew L. Schwaderer (Frontiers in Medicine, 2026)
Background Kidney transplant recipients are subjected to several types of immunosuppressants in order to prevent rejection of the graft. Over-immunosuppression increases the risk of infectious complications and thesepatients require a delicate balance. Inflammatory profiles from the urine can help identify which biomarkersmay guide clinicians in balancing over vs. under-immunosuppression. Methods Urine samples were obtained from 10 complete kidney donor-recipient pairs at a pre-operative visit ~1 weekprior to or at time of transplant and then for the recipients, ~3 months following transplantation. The urine samples were analyzed using inflammatory urine biomarker profiles (Mesoscale Discovery). Urine levels were then normalized to urine creatinine values. Differences were noted between groups using the mixed-measures ANOVA, corrected for multiple comparisons with the Tukey test to get adjusted p -values. Results Urine levels of TARC protein, also known as CCL17 and Tumor necrosis factor alpha (TNF- α ) were higher in patients with CKD than in donors or in the same patients post transplant. The antimicrobial peptide Ribonuclease 7 was higher in kidney transplant donors than recipients while Cathelicidin was higher in kidney transplant recipients than donors. Conclusion The urine inflammatory profile evolves over the transplant course between donors, pre-transplantrecipients and transplant recipients. Although the transplant itself is typically accepted as a pro-inflammatory event, levels of biomarks in the urine tend to decrease post-transplant. Immunosuppression regimens may influence inflammatory profiles and warrant further investigation.